Clinical and Epidemiological Aspects of Ankylosing Spondylitis Patients in a Single Center in Baghdad - Ali Hussein Al Hafidh (Journal of Techniques)
Ankylosing spondylitis is a chronic inflammatory disease with axial involvement but also may present as a peripheral arthritis and extraarticular manifestations.